Factors Related To Quality of Working Life of Workers in a Rubber Wood Processing Factory, Songkhla Province - Prommart, Chalita (Journal of Science and Technology Songkhla Rajabhat University, 2020)
The purpose of this research were to study the quality of work life among employees of rubber wood processing factory in Songkhla province, relationship between personal factors and quality of work life, relationships between support for safe working of organization and perception of work environment to quality of work life among employees of rubber wood processing factory in Songkhla province. The samples included 173 employees of rubber wood processing factory in Songkhla province and selected by using accidental sapling method. Data were collected through questionnaires. Statistical analysis included, percentage, average, standard deviation, Chi-Square, ANOVA and Pearson’s correlation coefficient. The result found that overall level of quality of work life among employees of rubber wood processing factory in Songkhla province was moderate. When considering each dimension of quality of work life the result showed that the benefit to society had the highest mean of score whereas the fair compensation was lowest mean of score. Furthermore the relationship between personal factors and quality of work life found that personal factors such as educational level, length of working and the accidental experience were related to the quality of work life statistically significant at the .05. The relationship between support for safe working of organization and quality of working life was moderate statistically significant at the .05. The relationship between perception of work environment and the quality of work life was moderate statistically significant at the .05.